Pengaruh Produk Tabungan Emas, Citra Merek Dan Harga Emas Terhadap Keputusan Nasabah Pada PT. Pegadaian (Studi Pada Nasabah Di Kantor Cabang Dieng Kota Malang) - Mochammad Zainul Arifin; Agus Widarko; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the effect of gold savings products, brand image and gold prices on consumer decisions at PT. Pawnshop in the Dieng Office of Malang City. This study used a quantitative type, data collection method using a questionnaire and a total sample of 95 respondents and using multiple linear regression analysis method which was processed with the SPSS program. The tests used to analyze the data are the research instrument tests (validity and reliability tests), the normality test, the traditional assumption tests (multicollinearity and heteroscedasticity tests), the test for multiple linear regression, the hypothesis tests (simultaneous test and partial test), and the adjusted R-square test of the coefficient of determination.The results of this study indicate that there is a simultaneous influence between the variables of gold savings products, brand image and gold prices on customer decisions of PT. Pegadaian an important value of 0.000 < 0.05. A significant value of 0.000 < 0.05 is associated with the gold savings product variable, a significant value of 0.001 < 0.05 is associated with the brand image variable, and a significant value of 0.000 < 0.05 is associated with the gold price variable for pawn shop customers. Keywords : Gold Savings Products, Brand Image, Gold Prices And Customer Decisions.